Investigation on the chipless RFID tag with a UWB pulse using a UWB IR-based reader. Issue 2 (12th March 2022) - Mekki, Kawther; Necibi, Omrane; Dinis, Hugo; Mendes, Paulo; Gharsallah, Ali
Abstract: In order to encrypt/encode data based on the magnitude level of the radar cross-section (RCS), we propose an approach with a precise estimation considering the resonant characteristics of a multipatch backscatter-based chipless radio frequency identification (RFID) dedicated for chipless tags depolarization. The working principle is based on the polarization mismatch between the tag and the reader antenna to control the magnitude of the backscatter, which allows a reliable detection in real environments. We introduce in this paper a new 4-bit chipless RFID tag with an enhanced RCS, based on a triangular patch antenna with multiple resonators. Additionally, we propose an ultra-wideband impulse radar (UWB-IR)-based reader that interrogates the chipless tag with a UWB pulse, and the received backscatter was studied in both time- and frequency-domains. The antenna was operating from 4.7 to 6.1 GHz, a band allocated for RFID systems. The obtained experimental measurement results in the environment of anechoic chamber were exceptionally relevant to validate the simulation results.